On the Heterogeneous Employment Effects of Offshoring - Identifying Productivity and Downsizing Effects - Moser, Christoph; Urban, Dieter; Weder di Mauro, Beatrice (Economic Inquiry, 2015)
This article examines the channels through which offshoring affects employment in a representative sample of German establishments, using a difference-in-differences matching approach. Offshoring is measured by an increase in the share of foreign to total intermediate inputs at the plant-level. We identify a positive productivity effect and isolate a negative downsizing effect from offshoring on employment, by exploiting differences between offshoring plants that do and do not simultaneously restructure. Furthermore, we cannot find evidence of negative indirect employment effects on domestic suppliers or competitor